Effect of Laser Heat Treatment on Microstructures of 1Cr5Mo Steel Welded Joint - GUO Wei; KONG De-jun; WANG Wen-chang (Cailiao gongcheng, 2017)
The surface of 1Cr5Mo heat-resistant steel welded joint was treated with CO2 laser,the microstructure and grain size grades of welded joints before and after laser heat treatment (LHT) were analyzed with 4XC type optical microscope (OM),and the distribution of residual stress and retained austenite content in the surface of the welded joints were measured with X-ray diffraction (XRD) stress tester.The results show that the grains of 1Cr5Mo steel welded joints are refined by LHT,and the microstructure uniformity improves significantly,the grain levels of welded zone,fusion zone,overheated zone and normalized zone increase from level 9,level 9.8,level 8 and level 10.7 to level 10,level 10.2,level 8.5 and level 11 respectively,the mechanical weak areas reduce from overheated zone,welded zone and fusion zone to the overheated zone.The tensile residual stress in the welded joint surface is eliminated by LHT and a layer of compressive residual stress with thickness of about 0.28mm is formed.The residual austenite content in the welded joint surface increases after LHT,of which the distribution is more uniform and conducive to the improvement of mechanical properties.